Effect of Bay Leaf Infusion on Microbiological, Chemical and Physical Quality of Chicken Meat - Edi Suryanto; Yuny Erwanto; Sylvie Astuti (Faculty of Animal Science, Universitas Gadjah Mada, 2020)
Contamination that decreased chicken meat quality could be prevented using natural preservatives. Bay leaves (Syzygium polyanthum) contain volatile fatty acids, tannin, and flavonoid that possess bacteriological and fungicidal activity as well as preventing bacterial spore growth. The purpose of this study was to determine the effect of fresh bay leaf infusion on microbiological, chemical, and physical qualities of chicken meat. This study used bay leaves, water, chicken meat, eight strain of bacteria, chemicals and materials for the analysis of chicken meat. The experiment consisted of two steps, the first was the antibacterial properties of bay leaves and the second was the application of bay leaf infusion for chicken meat. Eight bacteria was used for the bacterial inhibition of bay leaf at the concentration of 0, 5, 10, 15 and 20%. The experiment on antibacterial properties of bay leaf (Syzygium polyanthum) used one way randomized design with five concentration treatments, while the application of bay leaf infusions on chicken meat using factorial completely randomized design 2x5 (2 types of soaking and 5 observation time). At the second step, chicken meat was divided into 2 groups, the first group was soaked in water only and the second group was soaked in 15% bay leaf infusion. They were then stored for 0 (control), 2, 4, 6, and 8 hours at the room temperature. Each treatment was repeated four times. The microbiological, chemical, physical qualities of chicken meat were observed. The results showed that bay leaf infusion had the ability to inhibit the growth of bacteria (P<0.05). The highest growth inhibition was found on Leuconostoc mesenteroides, whereas the lowest growth inhibition was on Pseudomonas putida. Bay leaf infusion influenced the number of bacteria in chicken meat. The concentration of 15% bay leaf infusion could decrease bacterial number amounting to 1 log CFU/mL compared to control. The number of bacteria of chicken meat stored significantly increased during the storage (P<0.05). However, the number of bacteria of chicken meat soaked in bay leaf infusion was significantly lower than the control. Bay leaf infusion has no significant effect on the chemical quality of chicken meat but it did on the physical quality of chicken meat. The conclusion of the study was bay leaf infusion could inhibit the bacterial growth and reduced the amount of bacteria in chicken meat, whereas storage time influenced the microbiological and physical qualities of chicken meat.